Changes in intestinal microflora and its metabolites underlie the cognitive impairment in preterm rats - Lu, Xiang; Xue, Zhengyang; Qian, Yu; Wei, Shanjie; Qiao, Yu; Zhang, Wen; Lu, Hongyan (Frontiers in Cellular and Infection Microbiology, 2022)
Background The brain development of preterm infants is easily affected by various adverse extrauterine factors and complications, resulting in abnormal neurological and cognitive development. Recent studies have found that there is a significant correlation between intestinal microbial changes and cognitive behavior. Nevertheless, the correlation between the cognitive impairment and abnormal changes of intestinal microflora in the preterm newborn has been rarely elucidated. Aim To analyze the differences of fecal intestinal flora, short chain fatty acids (SCFAs) and microbiota-gut-brain axis (MGBA)-related serum factors between preterm birth with and without cognitive impairment. Methods Healthy female rats (body weight 410 ± 40 g) of 16-17 days of gestation were selected for the establishment of preterm cognitive impairment model and screened by Morris water maze navigation experiments. The pathological change of rat hippocampus was confirmed by HE staining. The abundance of fecal intestinal microflora was determined by 16sRNA sequencing, while the contents of fecal SCFAs were examined by gas chromatography. Results Compared with the control group, the cognitive impairment group had decreased abundance and diversity of intestinal microflora and increased abundance of Proteobacteria at the level of phylum. While the abundances of Alistipes, Bacteroides, Prevotella, and Lactobacillus decreased significantly at the level of order, family, and genus, the abundances of Staphylococcaceae, Enterococci, Psychrobacter, and Oligella increased significantly. Moreover, the levels of total SCFAs and acetic acid in the disease group were significantly lower. The fecal abundance of acetic acid was positively correlated with that of Lactobacillaceae or Peptostreptococcaceae, and negatively correlated with that of Aerococcaceae, and Alcaligenaceae in disease rats. Furthermore, cognitive impairment caused significantly decreased levels of 5-HT, GABA, and BDNF, and increased levels of GR, CRH, IL-6, and TNF-α in rat blood. Conclusion Alterations in intestinal microflora structure and the abundances of SCFAs contributed substantially to the cognitive impairment in preterm rats, which was associated with significant changes in MGBA-related soluble factors.